GEISMAS IR IŠSILAISVINIMAS G. DELEUZE’O IR F. GUATTARI POLITINĖJE FILOSOFIJOJE - Pocius, Kasparas (Problemos, 2011)
Straipsnyje bandoma atsakyti į klausimą, kaip Gilles’o Deleuze’o ir Felixo Guattari geismo samprata atsispindi jų politinėje filosofijoje. Tyrinėjama geismo mašinų ir jų gamybos koncepcija, jų santykis su sociumo struktūra ir kapitalo logika. Savo veikaluose šie du autoriai teigia, kad geismo mašinos kuria materialią revoliucinę energiją, kuri nuolat konfrontuoja tiek su sociumo normomis, tiek su kapitalistine priespauda. Tačiau, pasak jų, tokią energiją sociumas mėgina represuoti, paversti revoliucinį geismą fašistiniu „tvirtos rankos“ geismu, o kapitalas fetišizuoja, suprekina ir pritaiko savo tikslams. Šiame tekste, remiantis tiek Deleuze’o ir Guattari, tiek jų sekėjų tekstais, daroma prielaida, kad geismo mašinos sociumo represijoms ir kapitalistiniam suprekinimui gali priešintis pasirinkdamos atstumtųjų terpėje gimstančias kūrybingas ir radikalias mažosios politikos strategijas.Pagrindiniai žodžiai: geismas, geismo mašinos, sociumas, reakcija, kapitalas, suprekinimas, revoliucija, mažoji politika.Desire and Liberation in Political Philosophy of G. Deleuze and F. GuattariKasparas PociusSummaryThe article analyzes Deleuze and Guattari’s concepts of desire and desiring-machines, their origins and workings in the organized structure of socius and in the capitalist regime as well as the revolutionary strategies and milieus that these desiring-machines engender. Contemporary social critique often distorts the notion of desire while linking it exclusively with capital that forces people to consume identities and commodities. Meanwhile, in the conception of Deleuze and Guattari desire is a material revolutionary energy which constantly aims to confront the norms of both socius and capitalist repressions. Unfortunately, this energy is continually under the threat of being appropriated and inactivated by socius, and it also undergoes the risk of being fetishized and commodified by capital, which makes desire serve its aims of seeking profit and extracting surplus value. Desiring-machines attempt to break through to the other side of socius and capital, the former of which is decoded and deterritorialized, whereas the latter is too limited to deal with desire as an absolute limit of socius. Capital is unable to commodify potential revolutionary energy or to absorb it in another way. However, in the structure of socius active and creative desire may be reversed into reactionary fascist desire of hierarchy, exploitation, humiliation, slavery and death.The molar order of socius is distinguished by a clear structure and hierarchy where individuals have fixed identities. However, capital tries to demolish those structures and deterritorialize socius by following the desiring-machines. The discipline, laws and norms are substituted by the flexible axiomatic of capitalism, which (whenever possible) can adjust itself to the demands of desire or regenerate to the former repressive forms of command. Such milieu gives rise to a single monolithic molar class. Therefore, today the conflict lies not between the capitalist class and the working class but between the class and those who are outside the class – minor people, creating minor politics in molecular milieu.There is a paradox in the conception of minor politics by Deleuze and Guattari. Although this kind of politics originates in the space that is oppressed by socius and capital, however such space can become highly active, creative and radical. Desire as a material basis for creativity becomes a powerful revolutionary potential. Minor politics is based not on identification or representation of somebody’s interests, but on permanent creativity. This politics emerges within the milieu of mutual communication and intellect as well as uncommodified affectivity and sexuality and it embodies revolutionary desire in everyday practices of self-valorization.Keywords: desire, desiring-machines, socius, reaction, capital, commodification, revolution, minor politics.